Seizures as presenting and prominent symptom in chorea‐acanthocytosis with c.2343del VPS13A gene mutation. (27th January 2016) - Benninger, Felix; Afawi, Zaid; Korczyn, Amos D.; Oliver, Karen L.; Pendziwiat, Manuela; Nakamura, Masayuki; Sano, Akira; Helbig, Ingo; Berkovic, Samuel F.; Blatt, Ilan
Abstract: Objective: The aim of the study was to characterize the clinical features of nine patients in three families with chorea‐acanthocytosis (ChAc) sharing the same rare c.2343del mutation in the VPS13A gene. Methods: Genetic test results, clinical description, magnetic resonance imaging (MRI), and electroencephalography (EEG), as well as laboratory results are summarized. Results: ChAc is a rare genetic disorder characterized by hyperkinetic movements, seizures, cognitive decline, neuropsychiatric symptoms, and acanthocytes on peripheral blood smear. This unique cohort of nine patients is characterized by seizures as a first and prominent symptom. In our patients, other features of ChAc appeared later, including tics, other movement disorders, dysarthria, and mild to moderate cognitive decline. Significance: Patients with chorea‐acanthocytosis carrying the described rare mutation can present with focal, treatment‐resistant seizures.